LIGHTING IN CINEMATIC VIRTUAL REALITY - Ermo Säks, (PEOPLE: International Journal of Social Sciences, 2025)
With the emergence of inexpensive virtual reality (VR) head-mounted display (HMD) systems in recent years, VR has become commercially viable and more widely popular with some 200 million users worldwide. An important role in this take-up has been the development of cinematic virtual reality (CVR). As in any imagery, lighting design is one of the crucial elements in CVR that can greatly enhance the immersive experience in creating a desired look and feel and an engaging environment for the viewers to explore. However, there is currently very limited research on how set lighting can be and is used in CVR productions. This paper aims to fill this gap by reviewing the prevalent concepts for set lighting 360-degree videos which are companioned by examples by studying an existing CVR drama genre experience Wiktoria 1920. This paper investigates four set lighting strategies used in CVR: natural or ambient lighting, practical lighting, hidden lighting, and mixed lighting.